SEVERAL FACTORS AFFECT THE SPERM QUALITY OF VIETNAMESE MEN (Vietnam Journal of Community Medicine, 2022)
Background and Aims: Several studies have shown an association between age and BMIwith semen quality, but results have been inconsistent. In Vietnam, there is no research onthis issue. We carried out this study to investigate the relationship between age and BMIwith the semen quality of Vietnamese men.Methods: The cross-sectional descriptive study includes 1144 semen samples collected overfive years, from January 2017 to December 2021.Results: The 46-60-year-old group had significantly lower semen volume, total sperm count,and normal sperm ratio than the 16-30 and 31-45-year-old groups. The high BMI groupwas associated with lower semen volume and total sperm count than the other groups. Therelationship between the low BMI group and semen parameters is not clear.Conclusion: Aging decreased semen volume, total sperm count, and normal sperm ratio inpatients. High BMI decreased semen volume and total sperm count but reduced progressivemotility in patients.
Keywords: Age, BMI, Vietnam, sperm count, sperm quality.